PERAN LEMBAGA ADAT MELAYU (LAM) RIAU DALAM PELESTARIAN BUDAYA DAERAH DI PROVINSI RIAU. - Puti Bungsu; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Developing the culture in province is form the local government to keep Riau Malay culture. LAM Riau have a role to arranging a plan and managing the activity and developing custom activity too, art/ culture society, and making efficient use of culture assets and relic from history by inventorying. But this way still running not well. How does the LAM Riau roles in conservating Melayu Riau culture in Riau Province and what the factor that influence LAM Riau roles to conservating the culture in Riau culture. The concept of the theory used is organization development by Sondang P. Siagian (2012) to confronting the changes consist of education and commucation; participation; effort to expedite and give support, negotiation; and compulsion. This study uses qualitative methods research with descriptive data analysis. The author uses data collection techniques interviews, observation, and library studies. With the use of Key Informants as a source of information and using the technique of triangulation as a source in the vadilitas test data. Based on the result of the research, LAM Riau roles to conservating the culture in Riau province hasn’t been done optimally, it is still an implementation the roles which has not been reached, like participation to society generally still far from our prospect, negotiation between the manager is so not binding. Factors that affect the implementation of the strategy are human resources have not been sufficient good, e lack of funds owned, andd determining authority or policy that can not made by LAM Riau. Keywords: Organization Development, Conservating, Malay Culture